Deoxynivalenol mycotoxin dietary exposure on broiler performance and small intestine health: A comprehensive meta-analysis - Chala Adugna; Kai Wang; Jian Du; Chunmei Li (Poultry Science)
The effect of DON mycotoxins on broiler production performance and the small intestine is a critical factor in the health and well-being of broilers. Several studies have been conducted on this topic and have reported varying results and conclusions. Therefore, it is necessary to conduct systematic reviews and meta-analyses to thoroughly examine and draw unique conclusions. In this meta-analysis, we conducted a systematic review of multiple studies on the effects of DON mycotoxins in broilers. The analysis comprised 26 articles from reputable journals, and 14 parameters were identified based on the predetermined criteria. The forest plot results showed that DON treatment significantly reduced the ADFI and ADWG (SMD-1.50, 95 %CI [-1.68, -1.18]; I2= 51 %; p < 0.00001) and affected FCR (SMD 0.95, 95 %CI [ 0.62, 1.28]; I2= 77; p < 0.00001). In addition, it affects the small intestine structure duodenum (SMD -3.46, 95 %CI [-3.88, -3.05]; I2= 48 %; p < 0.00001), Jejunum (SMD -5.35, 95 %CI [-5.86, -4.83]; I2= 62 %; p < 0.00001), Ileum (SMD -2.6, 95 % CI [-3.12, -2.08]; I2= 82 %; p < 0.00001). Furthermore, DON exposure affects immunoglobulin (SMD -1.92, 95 % CI [ -2.39, -1.46]; I2 = 54 %; p < 0.00001) and antioxidant activities (SMD -2.1, 95 % CI [ -2.45, -1.75]; I2= 47 %; p < 0.00001). The overall effect of DON treatment was statistically significant compared with that of the control group. Furthermore, funnel plot analysis for publication bias did not reveal any significant asymmetry in most included studies. The results of this meta-analysis indicate that DON mycotoxins have a significant impact on both production performance and small intestine health and require strategic intervention.